Effect of Different Positions of Waveguide Port on the Coupled Model of Electromagnetic Wave and Heat Transfer in Microwave Heating of Coal - Deepshikha Bhargava; Phadungsak Rattanadecho (Science & Technology Asia, 2022)
Microwave heating has been used in coal processing for quite some time due to its low cost and time, and the ability to enhance the overall efficiency of the coal. Microwave ovens are widely used in microwave heating to understand the interaction between the microwaves and coal. A waveguide port, attached to the microwave oven, is responsible for the generation of the microwave radiation within the cavity. Its distance from the object placed inside the oven can affect the outcomes of the microwave heating. Therefore, it is important to study the effect of the waveguide position on the microwave heating of coal. In this paper, a coupled model of electromagnetic wave propagation and heat transfer is solved for a coal sample placed inside a microwave oven. The waveguide port is moved at a step of 10 cm for 15 positions, starting from the top of the left-side wall of the microwave oven up until above the glass table. Electric field intensity and temperature inside the microwave oven for each varied position of the waveguide port is calculated. An alternate pattern of increase and decrease in power absorption by the coal depending on the distance of the waveguide port has been observed. The highest power absorption occurs when the waveguide port is at one of the furthest positions from the coal.